The effect of planting media composition and provision of liquid organic fertilizer on the growth of Casuarina junghuhniana seedlings. Issue 1 (October 2020) - Gana, P; Paembonan, S A; Umar, A
Abstract: The purposes of this study were to determine the effect of planting media composition and liquid organic fertilizer concentration as well as their interactions on the growth and quality of Casuarina junghuhniana seedlings. The experimental design used a completely randomized design (CRD) factorial experiment with five replications. The first factor was the planting media with the composition of topsoil (control), topsoil:sand:husk charcoal (1:1:1), topsoil:sand:husk charcoal (1:2:1), topsoil:sand:husk charcoal (1:1:2), topsoil:sand:husk charcoal (2:1:1). The second factor was liquid organic fertilizer with a concentration of 0 ml (control), 100 ml/10 liters of water, 200 ml/10 liters of water, 300 ml/10 liters of water, 400 ml/10 liters of water. Growth variables observed were height, trunk diameter, number of leaves, top root ratio, and seedling quality index. Then, data were analyzed with the HSD at a 5% confidence level. The results showed that the treatment of planting media combination with topsoil:sand:husk charcoal (2:1:1) and liquid organic fertilizer concentration of 400 ml/10 liters of water had the best responses.